Spontaneous Vaginal Delivery of an Average Sized Dead Baby with Hand Prolapse at Term: A Case Report - Dhakal, Samjhana (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5065 NJOG 2010 Jul-Aug; 5(1): 58-59